Performance Enhancement in Compact Inverted-L Antenna by Using 1-D EBG Ground Structures and Beam Directors - Jae-Yeong Lee; Jaehyun Choi; Jae-Hyung Jang; Wonbin Hong (IEEE Access, 2019)
This paper describes a compact inverted-L antenna (ILA) topology that can enhance antenna performance by utilizing one-dimensional electromagnetic bandgap (1-D EBG) ground structures and two-stage beam directors. The antenna is fed through the coaxial connector and the microstrip line, and the 1-D EBG structures are embedded on the ground plane edge of the microstrip line that is closer to the planar ILA. The 1-D EBG ground structures serve as high impedance surfaces with slow-wave behavior controlling both reflection phase in plane-wave illumination and surface-wave on the horizontal-direction of the ground plane edge. The proposed antenna with 1-D EBG ground structures exhibits a wide impedance bandwidth of 810 MHz between 2.24 GHz and 3.11 GHz within a compact size of 0.21λ0 × 0.32λ0. In addition, the endfire radiation performances in horizontal-polarization of the designed antenna can be enhanced without any supplementary circuits by the integration of 1-D EBG structures within compact real-estate and by placing beam directors. As the criterion for improvement of the radiation pattern, the horizontally polarized end-fire gain of 4.0 dBi and radiation intensity difference between co-polarization and cross-polarization of 14.0 dB toward the end-fire direction are experimentally ascertained.